Realistic Scenario Based VANET Analysis through Sumo and NS3 - Zaidi, Taskeen; Giri, Shubhang; Srivastava, Kavita; Chaurasia, Shivam (International Journal of Sensors Wireless Communications and Control, 2018)
Background & Objective: Vanet is ad-hoc or temporary network that supports vehicle to vehicle or vehicle to infrastructure communication. Nowadays due to the exponential rise in road traffic and accidents, it is necessary to have information about vehicle position, speed, direction, lane etc. that aware us from traffic, road condition etc. to avoid accidents. Research has been going on in the field of traffic congestion problem, mobility model and Intelligent Transportation System (ITS). Method: To solve this complex problem a traffic simulator and a realistic scenario is needed but the issue is generating a realistic traffic scenario. Current work is focussed in this direction for building a realistic scenario of an area. Conclusion: In the current work, a realistic simulation in VANET is described and SUMO traces are integrated on network simulator-NS3.
Keywords: Vanet